The Existence of Nahdlatul Ulama Da'wah in the Era of Digitalization and Disruption - Murharyana; Al Ayyubi, Ibnu Imam; Suryana, Irfan; Andirani, Anita; Masfuroh, Ai Sri; Nurafiah; Noerzanah, Firda (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
This research aims to generalize and find things that are implicit in the world of da'wah in the era of digitalization and disruption of the largest community organization in Islam, namely Nahdlatul Ulama. This research uses a qualitative descriptive approach to examine the problematics and focus on the research conducted. the focus of this research is to obtain elementary information about the scope of social reality towards the existence of Nahdlatul Ulama da'wah integrated with the digital world and disruption. In this study, it is found that in preaching there are various problems faced today, such as competition, significant social change, and confrontation between groups. Regulation in preaching, Nahdlatul Ulama highly prefers digital platforms to provide relevant and conformist canalization to the community while maintaining the noble values of its founders to contemporary times. Thus, the existence of Nahdlatul Ulama is maintained and sturdy for generations, despite the modernization and westernization inherent in the aspects of globalization, besides the quantity and quality of Nahdlatul Ulama looks increasingly expansive geographically. Therefore, further research is expected to provide new insights into the influence of Nahdlatul Ulama in the religious aspects of society both in the aspect of da'wah in the world of digitalization which is implied in the education of Muslims.